The Leadership Role of the Principal as Supervisor in Conflict Management at Muhammadiyah 2 Madiun High School, East Java, Indonesia - Nurfaza Aula; Afiful Ikhwan; Nuraini Nuraini (Al-Hayat Al-Istiqomah Foundation, 2020)
The purpose of this study was to find out how the role and implications of the principal in carrying out his role as a leader, supervisor and administrator in combating conflict in educational institutions. This type of research is a qualitative descriptive study. The results of this research which is focused on SMA Muhamadiyah 2 Madiun are that as leaders, supervisors, and administrators have been going well. As for the supporting factors for the principal in carrying out his role, namely teachers, students, programs or plans, and curriculum, the inhibiting factors are discomfort in making decisions, facilities and infrastructure, teachers who do not have maximum scientific discipline, funding standards are still minimal, and the number of students who little influence on the financing standards of operational assistance funds received. Conflict resolution is carried out by the principal by means of deliberation and taking the middle way, advising, strengthening ties of friendship, compromising everything with various parties.